2019
DOI: 10.1080/15476286.2019.1624469
|View full text |Cite
|
Sign up to set email alerts
|

CircNAPEPLD is expressed in human and murine spermatozoa and physically interacts with oocyte miRNAs

Abstract: Circular RNAs (circRNAs) have a critical role in the control of gene expression. Their function in spermatozoa (SPZ) is unknown to date. Twenty-eight genes, involved in SPZ/testicular and epididymal physiology, were given in circBase database to find which of them may generate circular transcripts. We focused on circNAPEPLDiso1, one of the circular RNA isoforms of NAPEPLD transcript, because expressed in human and murine SPZ. In order to functionally characterize circNAPEPLDiso1 as potential microRNA (miRNA) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 85 publications
3
43
0
Order By: Relevance
“…Our data strongly suggest that SPZ-derived circNAPEPLD may function as a decoy to inhibit the anti-proliferative activity of some oocyte-derived miRNAs, thus allowing cell proliferation, a massive event during the first stages of embryo development [283]. As strongly suggested for other circRNAs, circNAPEPLD also appears to be able to bind RBPs.…”
Section: Sperm-derived Circrnas: Potential Modulators Of Sperm Qualitsupporting
confidence: 72%
See 3 more Smart Citations
“…Our data strongly suggest that SPZ-derived circNAPEPLD may function as a decoy to inhibit the anti-proliferative activity of some oocyte-derived miRNAs, thus allowing cell proliferation, a massive event during the first stages of embryo development [283]. As strongly suggested for other circRNAs, circNAPEPLD also appears to be able to bind RBPs.…”
Section: Sperm-derived Circrnas: Potential Modulators Of Sperm Qualitsupporting
confidence: 72%
“…Interestingly, human and murine SPZ retain two circular isoforms of NAPEPLD (that we named circNAPEPLDiso1 and circNAPEPLDiso2). Both isoforms are expressed at low levels in testis and heterogeneously fluctuate in sperm samples analyzed suggesting that, as for genetic traits, an individually variable transmission of epigenetic traits may exist as well [283]. Otherwise than previously reported, circNAPEPLDiso1 and circNAPEPLDiso2 expression appears to be independent from the linear counterparts, although there is evidence demonstrating a competition between circRNAs and linear transcripts [230,233].…”
Section: Sperm-derived Circrnas: Potential Modulators Of Sperm Qualitmentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, Chioccarelli et al () detected 10,726 transcripts in human spermatozoa by circRNA microarray. Ragusa et al () found that circNAPEPLDiso1 may represent a paternal cytoplasmic contribution to the zygote and may function as a miRNA decoy inside the fertilised oocytes to regulate the first stages of embryo development. In this study, five circRNAs (hsa_circ_0003812, hsa_circ_0001337, hsa_circ_0000816, hsa_circ_0000817 and hsa_circ_0000917) were predicted to be sponges of hsa‐miR‐206, and the circRNA‐hsa‐miR‐206‐mRNA network was generated as shown in Figure d.…”
Section: Discussionmentioning
confidence: 99%